2019
DOI: 10.1111/jne.12711
|View full text |Cite
|
Sign up to set email alerts
|

Maternal social environment affects offspring cognition through behavioural and immune pathways in rats

Abstract: The social environment of lactation is a key etiological factor for the occurrence of postpartum disorders affecting women and their children. Postpartum depression and anxiety disorders are highly prevalent in new mothers and negatively affect offspring’s cognitive development through mechanisms which are still unclear. Here, using a rat model, we manipulated the maternal social environment during lactation and explored the pathways through which social isolation (vs. the opportunity for limited social intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Social isolation also produces sexually dimorphic responses when it comes to sexually dimorphic reproductive behaviors. The social isolation of lactating female mice and rats reduced the duration of maternal care [ 161 , 162 ], while the isolation of male mice actually induced paternal behaviors toward unfamiliar pups and, in line, reduced their typical infanticide response [ 163 , 164 ].…”
Section: Sex Differences In the Response To Social Isolationmentioning
confidence: 99%
“…Social isolation also produces sexually dimorphic responses when it comes to sexually dimorphic reproductive behaviors. The social isolation of lactating female mice and rats reduced the duration of maternal care [ 161 , 162 ], while the isolation of male mice actually induced paternal behaviors toward unfamiliar pups and, in line, reduced their typical infanticide response [ 163 , 164 ].…”
Section: Sex Differences In the Response To Social Isolationmentioning
confidence: 99%
“…Elevated ICAM-1 in the brain has been shown in other murine neurolupus models. 53 Previous work has shown that high levels of ICAM-1 are detrimental to cognition 47 , 48 , 49 but again, this relationship is not clear-cut and neurolupus mice given anti-ICAM antibodies did not show attenuation of inflammation in the choroid plexus. 50 …”
Section: Discussionmentioning
confidence: 96%